Implementation Of Generator Grounding Parameters Through Distribution Transformer Using Labview - Ayu Fitriani; Muhammad Fadlan Siregar; Syafriwel Syafriwel (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
Determination of the generator neutral grounding system through a distribution transformer can be done through manual calculations. Many parameters are considered in the calculation to obtain the appropriate result there is the possibility of repeated calculations. This is very difficult and causes a large difference in the calculation results. Therefore, a computer-based computing system is needed to overcome these problems. Several papers have developed the calculation of the required generator neutral grounding quantity which considers the voltage level, short circuit fault current, and protection system against ground faults. This paper makes modeling in designing a neutral ground generator using the LabView Graphical User Interface (GUI) application. The goal is to make it easier, faster, and more accurate. As the implementation of the modeling used data from std C62.92.2TM-2017.